High gain over an octave bandwidth class-F RF power amplifier design using 10W GaN HEM - Noor Syakirah Ruslan Hadi; Zubaida Yusoff; Md. Golam Sadeque; Shaiful Jahari Hashim; Muhammad Akmal Chaudhary (Bulletin of Electrical Engineering and Informatics, 2020)
The wireless communication industry grows faster each day. In terms of RF power amplifier (RFPA), the requirements on efficiency, linearity, bandwidth, output power and cost are getting more stringent. RFPA is considered as the most important component because of consuming large power in a base station. In this paper, a systematic approach is used to design a high flat gain class-F RFPA over an octave bandwidth. The simulation of a 1.5GHz class-F power amplifier mode demonstrates a high drain efficiency while accomplishing a high flat gain over a wide bandwidth. To identify the optimum impedance for the output matching and input matching network, the load-pull and source-pull are performed. The simulation results show that the RFPA can deliver a drain efficiency of 68.37 % at the output power of 40.79 dBm with power added efficiency of 66.94 %. The designed PA achieved a high gain between 13 dB to 17 dB from 0.5 GHz to 2.0 GHz of a frequency band. The matching circuits are realized on an FR-4 substrate to keep the cost as low as possible. A 10W GaN HEMT CGH40010 transistor from Cree has been used for this RFPA design.